2018
DOI: 10.12968/jowc.2018.27.2.91
|View full text |Cite|
|
Sign up to set email alerts
|

An observational study of a superabsorbent polymer dressing evaluated by clinicians and patients

Abstract: The SAP dressing was well tolerated and shown to be effective in the management of moderate-to-high exudate. Consequently, the dressing supported improved healing, and reduced damage to periwound skin, leading to lower pain levels. Overall, both the patients and clinicians rated the SAP highly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…Simultaneously, the cost of care is reduced compared with a mix of other dressings. In a cost‐description analysis from the UK, Barrett 2018, found that treating 10 patients for 2 weeks with a superabsorbent dressing led to cost savings of £1179, compared with patients' total costs in the 2 weeks before the start of the study 34 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Simultaneously, the cost of care is reduced compared with a mix of other dressings. In a cost‐description analysis from the UK, Barrett 2018, found that treating 10 patients for 2 weeks with a superabsorbent dressing led to cost savings of £1179, compared with patients' total costs in the 2 weeks before the start of the study 34 …”
Section: Resultsmentioning
confidence: 99%
“…Of the 14 publications identified in the clinical SLR, the majority were case series ( n = 11), 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 with one RCT, 43 one retrospective matched observational cohort study, 44 and one retrospective cohort study 45 (Table 1 ). The most common country of origin was the United Kingdom (UK) ( n = 8).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have highlighted the varied ways in which healthcare professionals seek to measure and minimise patients’ pain 7–12. For example, an Irish study investigated nurses’ knowledge of wound management in relation to dressing change and pain (n=100) 12.…”
Section: Introductionmentioning
confidence: 99%